(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Review of the research and the reality of the costs of the survey and exploration in the oil exploration company The study showed the effect of the application of standard financial reporting (6) "mineral resources exploration and evaluation" on the financial statements, have touched on a range of problems, the most important deficiencies in the disclosure of information relating to expenses of research and exploration that must be show Kmugod and which should be recognized as an expense in the financial statements of the company based on the international standard (6) for the purpose of knowing the financial situation of the company, and to find solutions presented researcher hypothesis is the following: that the Company’s application standard financial reporting (6) will lead to the adequacy of audit programs, and this is what makes the company’s accounts and of the balance sheet and as a result of activity give a true and fair view of the financial position at the end of the period and in the light of this research found the conclusions of the deficiencies stated in the disclosure of the survey and exploration expenditures Kmugod trader (stock) which does not appear in the statement of financial position h / production stocks within the inventory account, leading to the loss of credibility of the financial position of the company, as the research found the recommendations refer to the need to adopt the audit of the research stage program of exploration form in which it helps to understand the reality of expenses research and exploration and knowledge of the financial situation of the company research sample as well as the importance of this program for the auditor to express an Technical neutral opinion on the financial statements of the company.